1983
DOI: 10.1002/mus.880060808
|View full text |Cite
|
Sign up to set email alerts
|

The CO‐dispersion index for the measurement of fiber type distribution patterns

Abstract: There is a need for a practical and statistically manageable quantitative index of fiber type co-dispersion in skeletal muscle to allow investigation of the distribution of motor units in normal muscle and their rearrangement in pathological states. A new measure for this purpose, the Co-Dispersion Index (CDI), is introduced. This measure is based on contingency table analysis of nearest-neighbor relationships between muscle fibers. The CDI has a continuous range of values from -1 to +1, in which larger negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The normal muscle tissue has a mosaic distribution of different muscle fibre types (Lester et al, 1983). Generally, a fibre type is randomly dispersed among other types in the muscle fascicle (Lester et al, 1983;Venema, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The normal muscle tissue has a mosaic distribution of different muscle fibre types (Lester et al, 1983). Generally, a fibre type is randomly dispersed among other types in the muscle fascicle (Lester et al, 1983;Venema, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The normal muscle tissue has a mosaic distribution of different muscle fibre types (Lester et al, 1983). Generally, a fibre type is randomly dispersed among other types in the muscle fascicle (Lester et al, 1983;Venema, 1988). However, the first quantitative examination of the fascicle structure showed that the peripheral part of fascicles in the extensor digitorum longus muscles of rat, cat and rabbit were predominantly composed of type II fibres (James, 1971).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of methods have been employed to describe the spatial distribution in whole fascicles (Jennekens et al, 1971;Lester et al, 1983;Lexell et al, 1983;Paton and Zucker, 1983;Grotmol et al, 1988;Venema, 1988). Another approach has been to divide the fascicle and count the different types of muscle fiber in each layer (Sjøstrøm et al, 1986;Grotmol et al, 1988;Pernus and Erzen, 1991;Strøm and Holm, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Lester et al, 3 in 1983, utilized the codispersion index to measure fiber type distribution in skeletal muscle. They point out the unreliability of unaided visual examination in judging fiber type clustering, noting the high rate of interobserver variability.…”
Section: Introductionmentioning
confidence: 99%